Content validity of a sustainable food management assessment instrument for island hotels using I-CVI and mean analysis - Azli Syam, Nur Alyasyahira; Isa, Nor Kalsum Mohd; Yunos, Mohd Yazid Mohd; Isa, Nor Junainah Mohd; Sormin, Darliana (Springer Nature, 2026)
This study aimed to develop and validate a research instrument for assessing sustainable food management (SFM) practices in island-based hotels. Data were collected to address the unique challenges of managing food operations sustainably in geographically isolated settings, characterized by supply chain constraints and reliance on imported products. The instrument was developed using indicators identified through a systematic literature review and evaluated by five experts from academia and industry using the item content validity index (I-CVI) and mean analysis. While several items were adapted from existing sustainability instruments, the present study introduced a novel contextual integration by tailoring the measurement to island hotel operations an area rarely addressed in previous hospitality research. The final instrument comprised 45 items across six operational domains: purchasing, preparation, storage, presentation, waste management, and food and service safety. Results indicated that most items achieved high I-CVI values (≥ 0.78) and mean scores (≥ 4.00), demonstrating clarity, contextual relevance, and practical applicability. The findings provide practical support for industry stakeholders and policymakers in monitoring, benchmarking, and improving sustainability performance, particularly in alignment with sustainable development goal 12 (SDG 12) on responsible consumption and production.